Navigating the digital landscape: teachers' digital repertoires in an under-resourced Cape Flats primary school - Dudley, Mark (School of Education, 2025)
This small case study examines the digital repertoires of two teachers in a Cape Flats Primary School as they attempt to take hold of digital resources and integrate them into their daily teaching practices. It draws on the interconnected socio-material theories of spatiality, assemblage and affect to provide a framework within which their entanglement with digital technology in an educational setting can be observed, described and analysed. The research focuses on the simultaneous array of challenges and opportunities which the teachers navigate in the process of acquiring, using and adapting a range of resources across various semiotic modes in the classroom space. This space is conceptualised in the study as a dynamic ecosystem where social, material and affective factors dovetail. It is also here where the digital repertoire emerges in situ, lying at the intersection between the teachers' skills, knowledge and experiences with technology and the material resources, infrastructure and cultural practices that exist within their school domain. The notion of the digital repertoire offers this study a dynamic lens through which to view the complexities, contradictions and tensions that arise as the teachers struggle to align their literacy practices and pedagogical approaches with their developing repertoires. This study challenges neoliberal ideas in which technology is viewed as a panacea for a South African education system uniquely skewed along the lines of social class, race, ethnicity, income, age and gender. It is critical of the kinds of deterministic thinking that currently influence digital intervention policies and strategies in South African education precisely because such determinism sacrifices socio-material context in favour of technical skills. In contrast, drawing on findings from the research, this study advocates for an approach to the integration of technology in classrooms that recognises the dynamic interplay of human agency, material resources and social contexts in shaping teachers' digital repertoires. The findings of this study therefore emphasise the need for personalised, context-aware and participatory professional development that empowers teachers to critically evaluate and meaningfully integrate technology into their teaching practice.